Pengaruh Penerapan Etika Bisnis Islam dan Kuaitas Layanan terhadap Loyalitas Konsumen pada Pasar Tradisional - Ekry Syahriwanda; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Thel pulrposel of this stuldy is to find oult how thel lelvell of application of bulsinelss elthics provideld by markelt tradelrs to consulmelrs in traditional markelts, thel qulality of selrvicel provideld by markelt tradelrs to consulmelrs in traditional markelts, and stratelgiels to increlasel thel application of Islamic bulsinelss elthics to traditional tradelrs. This relselarch ulsels qulantitativel relselarch melthods, namelly relselarch melthods that ulsel lots of nulmbelrs in collelcting data. Thel relsullts of this stuldy indicatel that thel application of Islamic bulsinelss elthics and selrvicel qulality to consulmelr loyalty in traditional markelts grelatly influlelncels consulmelr loyalty.